Blood on the Plaza - Ana Canales-Molina (The Toro Historical Review, 2024)
Exploration of the pivotal events surrounding the Tlatelolco Massacre of October 2, 1968, and its profound impact on Mexican society, politics, and international relations. The research delved into the complex dynamics leading up to and following the tragic event, examining the role of student activists, and the actions of the Mexican government under President Gustavo Díaz Ordaz, and the broader implications for issues of social justice and governmental control of social classes, not only in Mexico but globally.